Evaluation of Early and Late Tracheostomy Applications in Intensive Care Patients Before and After the COVID-19 Pandemic: Four-year Tertiary Center Experience - Kadir Arslan; Ayça Sultan Şahin (Türk Yoğun Bakim Derneği Dergisi, 2024)
Objective: The Coronavirus disease-2019 (COVID-19) pandemic has resulted in a critical need for optimal tracheostomy time. This study investigated the effects of early and late tracheostomy procedures performed in a tertiary center’s intensive care unit (ICU) on patient outcomes and mortality during the four years before and after the COVID-19 pandemic. Materials and Methods: This retrospective cross-sectional study included patients who underwent percutaneous tracheostomy in the ICU between March 2018 and March 2022. Patients were classified into Group 1 (early <10 days) and Group 2 (late ≥10 days) and evaluated before and after the COVID-19 pandemic. Demographic data, clinical features, and mortality were analyzed. Results: A total of 137 patients were included in the study. Among the study population, 62% were male, and 29.1% underwent early tracheostomy. Although the mean age of patients in Group 1 and the length of stay in the ICU were significantly lower, no significant difference was found between the groups in terms of mortality. Cranial pathologies were the most common indication for ICU hospitalization among patients who underwent tracheostomy before the pandemic, whereas COVID-19 was observed during the pandemic period. The COVID-19 pandemic had no significant effect on early-late tracheostomy rates, length of stay in the ICU, and mortality. During the pandemic, there was a significant difference in mortality among patients with cranial pathology. Conclusion: Early tracheostomy application decreased the length of ICU stay but did not significantly affect mortality. In addition, we found that the COVID-19 pandemic did not significantly affect mortality, except for early-late tracheostomy rates and patients with cranial pathology.